Kajian terhadap pelbagai teknik pengekstrakan minyak pati dari tanaman nilam (pogostemon cablin benth) - Asdarina, Yahya (2011)
Patchouli is a natural forest crop which contains essential oil of high value and with overwhelmed demand especially from the perfumery, cosmetics, and alternative medicines industry. The extraction of patchouli oil is still conducted via traditional method, with less emphasis on increasing the efficiency of the system, quality and optimizing the operating condition so as to operate the system efficiently. This study focused on developing the most effective method of extracting patchouli oil which able to produce the highest yield the shortest period of time. In addition, study was also conducted to examine the method of sample preparation and the effect of extraction time on the effectiveness of the system. Three methods of extraction and three types of sample were investigated, namely hydro distillation, steam distillation and combination of ultrasonic pretreatment with hydro distillation, with original or unaltered sample, cut sample, and ground sample, respectively. The outcome of the research revealed that steam distillation is a superior method of extracting patchouli oil, compared to the other two methods, and the usage of cut sample with extraction time of six hours produced the highest yield at 2.72%. Analysis via GC-MS showed that all methods of extraction examined in this study produced patchouli oil with quality surpassed the minimum requirement of commercial patchouli oil in the market. Optimization via application of Response Surface Methodology showed that the system can be represented by a linear model. From the model, experiment was conducted in accordance with the suggested maximum operating conditions, and the extraction yield was increased to 2.82%, which is 3.67% higher than the yield before the system was maximized